2019
DOI: 10.1136/ijgc-2018-000026
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision-making in elderly women with ovarian cancer: an age-based comparison

Abstract: ObjectiveTo investigate treatment choices and outcomes in women with ovarian cancer, comparing elderly (≥75 years) and younger patients (<75 years).MethodsA single-center retrospective analysis of patients diagnosed with ovarian cancer between 2010 and 2015. The initial treatment plan and course of treatment were extracted from medical files.ResultsOf 128 included patients, 34% were aged ≥75 years. The initial treatment plan consisted of the combination of cytoreductive surgery and platinum-based doublet chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The effect of this was illustrated in an ovarian cancer study, in which only 10% of patients aged over 75 years received best practice care according to guidelines (although the degree of patient involvement in these decisions was not specified). 9 This disconnect is acknowledged in NHS England's Cancer Strategy, which advocates a need to assess integrated pathways for older cancer patients, as well as better outlining the role of geriatricians and their input into the MDT. 10 What can comprehensive geriatric assessment offer?…”
Section: Shared Decision Making In Older Gynae-oncology Patientsmentioning
confidence: 99%
“…The effect of this was illustrated in an ovarian cancer study, in which only 10% of patients aged over 75 years received best practice care according to guidelines (although the degree of patient involvement in these decisions was not specified). 9 This disconnect is acknowledged in NHS England's Cancer Strategy, which advocates a need to assess integrated pathways for older cancer patients, as well as better outlining the role of geriatricians and their input into the MDT. 10 What can comprehensive geriatric assessment offer?…”
Section: Shared Decision Making In Older Gynae-oncology Patientsmentioning
confidence: 99%
“…These authors found that the CGA affected treatment decisions in a percentage of cases ranging between 21% and 49% [23][24][25][26]. Other studies have shown that incorporating the CGA in the management of older patients with cancer (i) improves clinical outcomes by helping select the most appropriate therapy [27], (ii) promotes the inclusion of patient preferences in the decision-making process [28][29][30], (iii) improves communication between oncologists and patients [28][29][30], (iv) reduces the risk of over-and undertreatment [31], (v) enhances treatment tolerance and completion [32] and (vi) predicts the frequency of hospitalisation and long-term care for older cancer survivors [33].…”
Section: Proponents Target Population Recommendationsmentioning
confidence: 99%
“…This loss of resilience may mean the difference between being independent in the aftermath of treatment, or becoming dependent so that hospitalisation or full-time care are now necessary. The patient's treatment decision may thus be impacted by such an outcome, as demonstrated in some studies to date [26,27].…”
Section: What Is Frailty?mentioning
confidence: 99%